Depression and pulmonary function in outpatients with asthma - Krommydas, Georgios C.; Gourgoulianis, Konstantinos I.; Angelopoulos, Nikiforos V.; Molyvdas, Paschalis Adam; Kotrotsiou, Evangelia; Raftopoulos, Vasilios (My University, 2004)
The purpose of this study was to examine the relation between depression, anxiety and pulmonary function in asthmatics. Thirty-eight adult asthmatic patients underwent psychometric evaluation with the DSSI/sAD questionnaire, filled in an asthma questionnaire and underwent spirometry. The majority of patients suffered from mild-persistent asthma. Twenty-six reported symptoms of anxiety and 25 reported symptoms of depression. A statistically significant reduction in FEV1 and FEV1/FVC values was observed in asthmatic patients with symptoms of depression. The mean value of FEV1 was 81.84(720.83) in patients without symptoms and 63.73(717.99) in patients with symptoms of depression. The mean values of FEV1/FVC were 0.85(70.11) and 0.75(70.10), respectively. These findings indicate a high frequency of depression and anxiety in adult asthmatic patients. A biological linkage between depression and impaired pulmonary function is proposed.
Keywords: Asthma; Anxiety; Depression